La cuestión social en Portugal: indicadores y retos para el Trabajo Social (2024)
Objective. Present a preliminary study of Portugal’s expressions of the social question, emphasizing its integration into the European Union and the analysis of indicators for monitoring the risk of poverty (EAPN, 2023). The aim is to advance in dealing with the social question as a permanent challenge for social work regarding its object, resulting from the historical movement of class struggle and deciphering its new and complex manifestations. According to the theoretical-methodological direction of the network research “Social Work in History: social question and social movements - Latin America and Europe.” Methodology. The social question is problematized in its historical distinction, the contradiction of capitalist social relations, the unity and antagonism between capital and labor, and its current expressions in Portugal. Results. The analysis showed that these expressions relate to precarious work conditions, unemployment, migration, and poverty. Conclusion. Greater protagonism is required from social workers for responsive intervention to social issue.